THE ROLE OF NUCLEAR POWER AND OTHER ENERGY OPTIONS IN COMPETITIVE ELECTRICITY MARKET STUDY USING MESSAGE MODEL - Scorpio Sri Herdinie; Edi Sartono (Jurnal Pengembangan Energi Nuklir, 2003)
ABSTRACT THE ROLE OF NUCLEAR POWER AND OTHER ENERGY OPTIONS IN COMPETITIVE ELECTRICITY MARKET STUDY USING MESSAGE MODEL. The electricity demand in Indonesia is very high due to the National Economic Development based on industrialization and supported by a strong agriculture base. It can be noted that in the last five years, the annual electricity growth rate has been reaching around 15% per annum. Though during the economic crisis the electricity demand have time to reduction. Start early 2000s the economic growth in Indonesia will gradually increase. As a consequence, the electricity growth rate also increase in the next coming decades. MESSAGE (Model for Energy Supply Strategy Alternatives and their General Environmental Impacts) is a model designed for the optimization of energy system (i.e. energy supplies and utilization). The goal of this study is to support the national planning and decision making process in the energy and electricity sector in Indonesia with regard to the economic, health, environmental and safety aspects. The objective of this study is to analyse the role of Nuclear Power Plant in the whole energy systems by introducing the new electricity regulation and structure in the market. Seen that Nuclear Power Plant will be enter the Java Bali system in the period between 2015-2020. and will dominate the addition of capacities by the end period of study (year 2020-2025). Nuclear energy has very important long term roles in the energy scenario and it is possible to do the market competitiive when the Multi buyer Multi Seller (MBMS) will be done in the system electricity in Indonesia (the government has changed the target of MBMS realization into 2007).   ABSTRAK STUDI PERAN PEMBANGKIT TENAGA NUKLIR DAN ENERGI LAIN DI DALAM KOMPETISI PASAR LISTRIK DENGAN MENGGUNAKAN PROGRAM MESSAGE. Tuntutan akan kebutuhan listrik Indonesia sangat tinggi dalam kaitan dengan Pengembangan Ekonomi Nasional berdasar pada Industrialisasi yang didukung oleh pertanian kuat. Hal ini dapat dilihat bahwa pada lima tahun terakhir, laju pertumbuhan listrik telah mencapai sekitar 15% tiap tahun. Meskipun selama krisis ekonomi, permintaan listrik sempat mengalami suatu pengurangan. Mulai awal 2000-an pertumbuhan ekonomi Indonesia secara berangsur-angsur meningkat. Sebagai konsekwensi, laju pertumbuhan listrik akan juga meningkat pada dekade yang akan datang. MESSAGE (Model for Energy Supply Strategy Alternatives and their General Environmental Impacts) adalah suatu model optimalisasi sistem energi (yaitu, penyediaan energi dan pemanfaatan). Tujuan dari studi ini adalah untuk mendukung proses pengambilan keputusan dan perencanaan energi nasional dan sektor listrik di Indonesia yang mempertimbangkan nilai ekonomi, kesehatan, lingkungan dan aspek keselamatan. Sasaran studi ini adalah untuk meneliti peran Pembangkit Energi Nuklir pada keseluruhan sistem energi dalam kaitannya dengan peraturan sistem pasar listrik yang baru. Hasil dari studi ini dapat disimpulkan bahwa pembangkit Listrik tenaga Nuklir akan masuk ke dalam Sistem Jawa-Bali pada periode tahun 2015-2020, dan akan mendominasi penambahan kapasitas pada periode akhir studi (tahun 2020-2025). Peran energi nuklir jangka panjang sangat penting di dalam skenario penyediaan energi khususnya listrik dan memungkinkan untuk berkompetitif dengan energi yang lain dalam menghadapi sistem pasar yang Multi Buyer Multi Seller (MBMS), jika sistem tersebut diberlakukan di Indonesia (pemerintah telah mentargetkan perwujudan sistem pasar MBMS pada tahun 2007).